Risk Management for 4-H Youth Development Work: Fundraising and Fundhandling - Dale Pracht; Alexandria Pennisi; Paula Davis; Stefanie Prevatt; Janet Psikogios (EDIS)
This 6-page document is one in the series Risk Management for 4-H Youth Development Work. It reviews policies and best practices for handling 4-H program funds and conducting 4-H fundraisers. Written by Dale Pracht, Alexandria Pennisi, Paula Davis, Stefanie Prevatt, and Janet Psikogios and published by the UF/IFAS 4-H Youth Development Department, January 2018. http://edis.ifas.ufl.edu/4h386